(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
A carbohydrate antigen called CA19-9 is used to identify pancreatic cancer patients. Pancreatic cancer patients and those with some other gastrointestinal carcinomas have been reported to have increased levels of CA19-9. Additionally, recent research suggests that this antigen plays an etiological function in pancreatitis and pancreatic cancer. Decreasing levels of the marker are indicative of a good prognosis and are commonly used to evaluate the effectiveness of therapies offered for pancreatic cancer. Lowering CA19-9 levels in patients with pancreatitis from the start of treatment has been demonstrated to be successful using Ayurvedic approaches. Research on this formulation as a preventive treatment for pancreatic cancer in people with pancreatitis may find fresh direction as a result of this observation. In this case report, the author and his team discuss Ayurvedic features of patient treatment through the use of Ayurvedic therapy. The pancreatitis patient with increased CA 19-9 levels who received treatment with Ayurvedic medicines is the subject of this report’s observations.